Contract farming, cooperatives and challenges of side selling: malt barley value-chain development in Ethiopia. Issue 4 (19th May 2021) - Alemu, Dawit; Guinan, Alice; Hermanson, Judith
ABSTRACT: This paper presents the experience of malt barley value-chain development through cooperative-based contract farming. The descriptive and qualitative analysis used primary data collected from the actors involved and secondary data. The results indicate that side selling is a major challenge, estimated at about 30%. Promoting the role of cooperatives and avoiding side selling by addressing both farmer- and system-level issues requires considering the dynamic nature of the malt barley market, involvement of all relevant stakeholders, capacitating cooperatives rather than providing handout-type support, and promoting market-based disincentives and incentives for the misconduct and conduct of actors.